2018
DOI: 10.1002/sd.1891
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale mining, spatial mobility, place‐making and development in the Peruvian Andes

Abstract: This paper focuses on population mobility dynamics in and around mining areas in the Peruvian Andes. We use a case study of Rio Tinto's La Granja exploration project in Cajamarca Region to highlight the complexity and fluidity of the population movements around that project and the significant level of agency exercised by local people, as well as how people have been impacted by corporate decisions. We argue that, far from being a relatively static system of social and production relationships, the Andes has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…After the Conga project was put on hold, heavy activism in Cajamarca largely died down. However, similar to Castillo and Brereton (2018)’s finding that, in terms of migration, even non-existing mining projects can permanently alter meaning-making regarding place, I argue here that local relationships between the urban and the rural may also be permanently altered through a shift in local meaning-making, in this case, as it occurred in the context of the non-realized Conga project.…”
Section: Belonging In Placesupporting
confidence: 77%
“…After the Conga project was put on hold, heavy activism in Cajamarca largely died down. However, similar to Castillo and Brereton (2018)’s finding that, in terms of migration, even non-existing mining projects can permanently alter meaning-making regarding place, I argue here that local relationships between the urban and the rural may also be permanently altered through a shift in local meaning-making, in this case, as it occurred in the context of the non-realized Conga project.…”
Section: Belonging In Placesupporting
confidence: 77%
“…Migration can be cyclical over time. Castillo and Brereton (2018) found that as job opportunities declined in the La Granja in the Andes, many families moved either to urban areas on the coast or rural lands in the lowlands. Often, older members of the family stayed behind to watch the land and property.…”
Section: The Complexity Of Migration: Cyclical Patterns and The Urbanmentioning
confidence: 99%
“…The contributors to this special issue all note the economic determinants of migration into mining communities. Castillo and Brereton () observe that there can also be an outflow as people use benefits to move to towns “precisely because they present greater economic opportunities and offer better services”. Their strategies draw on social capital and familial networks to do so.…”
Section: Managing Change and Migrationmentioning
confidence: 99%
“…They flourish while the mine is operating and people depart when it closes. Castillo and Brereton () suggest that migration in and out of a mining area in Peru is determined mainly by the opportunities for employment or economic benefit, but that movements are also to be understood in terms of kinship and relational networks. Certainly, the motivations and strategies vary, but in Papua New Guinea, the initial influx of migrants is usually made up of people who have moved away from their “undeveloped” location for employment and return when the possibility arises in their own place.…”
Section: Managing Change and Migrationmentioning
confidence: 99%